Small Aneurysms Account for the Majority and Increasing Percentage of Aneurysmal Subarachnoid Hemorrhage: A 25-Year, Single Institution Study. Issue 4 (6th October 2017) - Bender, Matthew T; Wendt, Haley; Monarch, Thomas; Beaty, Narlin; Lin, Li-Mei; Huang, Judy; Coon, Alexander; Tamargo, Rafael J; Colby, Geoffrey P
Abstract: BACKGROUND: Prospective studies of unruptured aneurysms have shown very low rates of rupture for small aneurysms (<10 mm) and suggested that the risk of treatment outweighs benefit. However, common clinical practice shows that patients with aneurysmal subarachnoid hemorrhage (aSAH) frequently have small aneurysms. OBJECTIVE: To investigate trends in size and location of ruptured aneurysms over a 25-yr period. METHODS: A prospective, Institutional Review Board-approved database of all patients presenting to our institution with aSAH from 1991 to 2016 was analyzed. Cerebral angiography identified the source of hemorrhage. Patients with nonaneurysmal etiologies were excluded. RESULTS: Complete data were available for 1306/1562 patients (84%) with aSAH from 1991 to 2016. The average age was 53 yr and 72% of patients were female. The average size of ruptured aneurysms over 25 yr was 8.0 mm. The average size of ruptured aneurysms decreased steadily with each 5-yr interval from 10.1 mm (1991-1996) to 6.6 mm (2012-2016; P < .001). Overall, very small aneurysms (<5 mm) were responsible for aSAH in 41% of patients. The percentage of very small ruptured aneurysms rose from 29% during the initial 5-yr period (1991-1996) to 50% in the most recent period. Likewise, the percentage of ruptured aneurysms that were 5 to 9 mm rose from 26% to 34% ( P < .001). In the past 5 yr, aneurysms <10 mm accounted for 84% of aSAH. Vessel of origin ( P = .097) and aneurysm location ( P = .322) did not vary with time. CONCLUSION: Ruptured small and very small aneurysms represent a majority and increasing share of aSAH. Identification and prophylactic treatment of these aneurysms remains an important clinical role for cerebrovascular neurosurgery.